(untitled) (Quinto Sol, 2024)
In late 1972, four rock operas were released in Argentina: Sudamérica o el regreso a la aurora by Arco Iris, Cristo Rock by Raúl Porchetto, Tontos (Operita) by Billy Bond and the Pesada del Rock and Roll and Ohperra vida de Beto de Materia Gris. In this paper, I analyze the music and lyrics of these records and a series of newspaper and magazine articles that commented on them. I examine in this way some of the biggest efforts made by Argentine rockers to bring their musical ambitions into dialogue with the discourses of protest and the expectations of social transformation that intensified precisely during those months in Argentina. How did Argentine rock participate in the process of social mobilisation and political radicalisation then underway? What could or should be the role of rock in those days of politicisation, according to rock musicians, rock fans and political activists? In responding to these questions, this paper contributes to the understanding of the links between youth, music and politics in Argentina in the 1970s.